A integração do design na indústria do mobiliário após a adesão à CEE - Silva, Vanessa (2018)
The context of this investigation is a study on the integration of design in the furniture making sector during the period of the national economy’s opening, by the end of the twentieth century. This work was undertaken through an approach focused on the effects of the country’s entry in the European Economic Community upon its industry and the strategies that were adopted by the furniture-making industries to face foreign competition. This study aims to understand the integration of design on the furniture making industry, within the context of the sector’s evolution after the country’s entry on the EEC. This is a pertinent research as studies on both Portuguese design and the national furniture making sector are very scarce, whereby it can serve as a basis for future reflections on how to undertake interventions within this sector. An attempt to contribute towards the theoretical development of the Portuguese design studies and its relation with the furniture making sector was thus made. Methodologically wise, this work resorted to qualitative analysis above all else. Literary revision was complemented with case studies related to the course of two national and furniture making corporations as well as a foreign one. In order to depict the industrial sector, the statistical data from the period between the 1990’s and 2015 were analyzed and tables and charts that allow a better reading of the displayed information. The furniture’s characterization was elaborated through the observation and analysis of images obtained in national home decoration magazines. This study also contains seven interviews that were made to representatives of corporations belonging to the sector and a chronological table that places the more important events related to design and the industrial development that touched upon during the course of this work side by side. The main conclusion concerns the problems of design’s integration in the furniture-making industry and the profession’s regulations. The effects of the country’s entry in the EEC have had opposite repercussions upon the development of the industry and design in itself. During the 1990’s, the industry had gone through a serious crisis period. Simultaneously, a great interest for design, as well as several financial resources that were used to support the promotion of this activity, appeared. Both these activities ended up developing separately